La qualification des contrats d'auteur - Raimond, Sébastien (Université Paris Est, 2008)
La qualification du contrat au regard du droit d’auteur met en exergue un renversement de la logique présidant habituellement à la construction des catégories contractuelles : les divers contrats nommés et, au-delà, tous les contrats d’auteur, sont moins définis par égard à leurs effets, à savoir le transfert de droit et les obligations qui en sont la contrepartie, que par référence à leur environnement. En effet, alors que l’effet translatif est commun à tout contrat d’auteur, sa qualification dépend avant tout de son environnement « matériel », c’est-à-dire du type d’oeuvre de l’esprit ou de droit d’exploitation visés au contrat, ou de son environnement humain, c’est-à-dire la qualité des parties, notamment celle d’auteur. À l’inverse de la qualification du contrat au regard du droit d’auteur, celle du contrat d’auteur au regard du droit civil dépend plus de ses effets que de son environnement, ce qui s’avère logique dès lors que les catégories contractuelles du code civil ne sont pas définies en fonction de ce dernier. Dès lors que la nature du droit d’auteur ne constitue pas un obstacle aux qualifications civiles, les effets du contrat constituent les seuls critères de distinction opératoires. Lorsque l’obligation d’exploiter ne peut être réduite à une obligation accessoire, la qualification de vente ne peut qu’être évincée. Les modalités de la maîtrise de l’exploitation font alors apparaître que les contrats d’édition, de représentation et de production audiovisuelle sont en réalité, le plus souvent, des contrats de bail.
Keywords: Author's contract; Contrat d'auteur; Copyright; Droit d'auteur; Droits voisins; Intellectual property; Propriedade intelectual; Propriété intellectuelle; Qualification; Qualification (droit)

Essai sur une théorie générale en droit d'auteur - Haddadin, Suhail (Université de Poitiers, 2008)
This study proposes a critical reading of the contemporary doctrinal and jurisprudential currents that under the influence of the Anglo-Saxon system make back-move on the fundamental concepts of author's right. It aims to show that the property of the author on his work is not a legal dogma, but a result of the general principles of the French civil law, even of the entire French legal system. From where, the idea that the moral right in its traditional structure, finds a base adequate in the French Civil code. The current debate, which opposes the "romantic" and pragmatic doctrines, provides the discussion thread of the development of a general theory of author's right.
Keywords: Abusus; Author's right; Droit d'auteur; Droit moral; Epuisement du droit de divulgation; Individualism; Individualisme; Intellectual property; Intérêt général; Jürgen Habermas; Legal theory; Moral Right; Philosophie du droit d'auteur; Private sphere/Public sphere; Propriété artistique; Propriété intellectuelle; Propriété littéraire; Sphère privée/Sphère publique; The Exhaustion of the right of disclosure; The philosophy of author's right; Théorie générale; Utilitarianism; Utilitarisme; Études comparatives

Explaining Copyright: The Normative Implications of its Sociotechnical Construction - Nicholson, Scott (Queen’s University, 2008)
The construction of copyright law can be causally explained by two possible types of explanation: dialectical explanations and material explanations. I argue that an adequate causal description of the copyright discourses of Western legal systems must incorporate a material explanation in order to account for many of the general and particular characteristics of the evolution of copyright. As a vast variety of contingent and interactive social and technical conditions have caused the evolution of copyright, we should expect a plausible material explanation to be multifaceted and multi-layered. However, in addition to providing a causal sociohistorical description, a good legal explanation should also seek to include a normative account detailing the moral grounds of the law, or lack thereof. Dialectical explanations can be teleological: they can presuppose that the law is directed towards a perfect legal state and that it is essentially guided by a set of moral ideals. Material explanations, on the other hand, are essentially non-normative and do not explicitly address moral questions. But this does not entail the elimination of moral considerations from material explanations. As I aim to show, we should not address the moral and sociohistorical elements of copyright legal discourses independently because they are causally connected: moral justifications have been rhetorically used by social actors to influence lawmaking processes, and conversely, changes in technical conditions have given rise to sociotechnical formations that enable and structure the norms of copyright. Given this, I propose that lawmakers should adjudicate and legislate from a broad and flexible standpoint. They should not attempt to merely apply old principles to new problems, but should comprehend new moral norms introduced by new conditions, and balance them against the older, more established principles enshrined in traditional intellectual property theories.
Keywords: Copyright; Intellectual property